PROSE OF GRIGORY GOUSEYNOV IN HRONOTOPNIH MEASURINGS: ON MATERIAL OF BOOK THE «STATION PASTORALS» - Chorob, M. B. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
The time and space features of prose of the known modern Ukrainian writer, laureate of Shevchenko bonus of Grigory Gouseynov are explored in the article. Mainly for the analysis an autobiographic story the «Station pastorals» is used.